Tourist experience of Indonesia’s tourism in the era of digitalization - Briandana, Rizki; Anggraeni Ananda, Ida; Mokhtarrudin Ahmad, Mokhtarrudin (Universitas Bunda Mulia, 2024)
Millennials are stakeholders as well as consumers of the tourism sector for a country. Millennials' needs, wants, habits, and behavior, especially regarding the use of new media in daily life, are seen as important things to pay attention to. Millennial characteristics, competitiveness and attractiveness of tourist destinations, and public relations are important concepts in this study. In this context, Malaysian tourists visiting Indonesia provided input regarding digital tourism in Indonesia. The main concepts used were Social Media and Digital Era for Tourism. Qualitative case studies were the research methodology in this study. The data collection technique used was in-depth interviews. The informants in this study were Malaysian tourists, totaling 6 people. The results show that the tourism experience of foreign tourists provides valuable information regarding the use of information and communication technology for better tourism in Indonesia.